2012
DOI: 10.1002/chem.201102786
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Stereochemically Active Lone Pairs For Influencing PbII and AsIII Protein Binding

Abstract: Heavy metal toxicity is a worldwide problem which is associated with the metal’s high affinity for thiolate rich proteins. Despite the tremendous toxicity concern, the mode of binding of As(III) and Pb(II) to proteins is poorly understood. To clarify the requirements for toxic metal binding to metalloregulatory sensor proteins such as As(III) in ArsR/ArsD and Pb(II) in PbrR or replacing Zn(II) in δ-aminolevulinc acid dehydratase (ALAD), we have employed computational and experimental methods examining these he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 83 publications
(73 reference statements)
5
60
0
Order By: Relevance
“…The model corresponding to the lowest computed energy was described with two endo Cys residues and one exo Cys residue, whereas the most energetically unfavorable conformer had two exo Cys and one endo . 712 Similar DFT results were also reported for Pb(II) complexation by these systems. EXAFS studies showed that both TRI L16C and TRI L12C bind As(III) with an As–S bond length of 2.25 Å, which is consistent with the reported values for ArsR (2.25 Å) and small molecule As(III)S 3 ligation site distances (2.20–2.33 Å).…”
Section: De Novo Designsupporting
confidence: 75%
“…The model corresponding to the lowest computed energy was described with two endo Cys residues and one exo Cys residue, whereas the most energetically unfavorable conformer had two exo Cys and one endo . 712 Similar DFT results were also reported for Pb(II) complexation by these systems. EXAFS studies showed that both TRI L16C and TRI L12C bind As(III) with an As–S bond length of 2.25 Å, which is consistent with the reported values for ArsR (2.25 Å) and small molecule As(III)S 3 ligation site distances (2.20–2.33 Å).…”
Section: De Novo Designsupporting
confidence: 75%
“…The steric consequences of the lone pair (Lp) of electrons on Pb(II) has been of enduring interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and there has been some doubt expressed even as to the existence of a stereochemically active Lp on Pb(II) [14,15,17]. Of interest here is that a study of the Tl(I) complex of 18-crown-6 (see Figure 1 for ligand abbreviations) has been used to suggest that there is no 6sp hybridization involved in producing what appears to be a stereochemically active Lp on the Tl(I) [17].…”
Section: Introductionmentioning
confidence: 99%
“…[7,14,15] Much of our effort and success in the de novo design field has been carried out using the 3SCC scaffold of TRI, [1631] Grand (Gr), [24,26,32,33] and BABY [18,33,34] peptides, as well as in CoilSer (CS), [22,27,28,33,3537] which serves as a crystallographic analogue for TRI (Table 1). A metal-binding site is generated by incorporating a cysteine or penicillamine residue at the “a” (Figure 2b) or “d” (Figure 2c) position in a 3SCC scaffold.…”
Section: Development Of De Novo Designed Scaffoldsmentioning
confidence: 99%
“…[37] We discovered that the subtle difference between the “a” and “d” positions can produce distinctive outcomes in heavy metal binding affinity and geometry, which can be attributed to the pre-organization of the sulfur ligands prior to metal binding. [14,17] Overall, we have gained a deeper understanding in the metallobiochemistry of heavy metals, such as As(III), [19,28,35] Cd(II), [14,1922,2426,32] Hg(II), [1619,22,23,25,27,34] and Pb(II), [21,28,33,38] in a tristhiolate site. We have demonstrated how to control the coordination number and geometry of Cd(II) [14,24,26,32] and Hg(II), [18,19,23,25] determined the affinity for Cd(II) [21] and Pb(II), [21,33] based on site preferences for “a” or “d” sites of the Cys residues, and elucidated the effects of the core aliphatic groups in the second coordination sphere on the molecular recognition of Cd(II) [14,24,26] and Pb(II).…”
Section: Development Of De Novo Designed Scaffoldsmentioning
confidence: 99%